Compact Assembly and Programmable Integration of Supercapacitors. Issue 6 (18th December 2019) - Lu, Bing; Liu, Feng; Sun, Guoqiang; Gao, Jian; Xu, Tong; Xiao, Yukun; Shao, Changxiang; Jin, Xuting; Yang, Hongsheng; Zhao, Yang; Zhang, Zhipan; Jiang, Lan; et al.
Abstract: Microsized supercapacitors (mSCs) with small volume, rapid charge–discharge rate, and ultralong cyclic lifetime are urgently needed to meet the demand of miniaturized portable electronic devices. A versatile self‐shrinkage assembling (SSA) strategy to directly construct the compact mSCs (CmSCs) from hydrogels of reduced graphene oxide is reported. A single CmSC is only 0.0023 cm 3 in volume, which is significantly smaller than most reported mSCs in fiber/yarn and planar interdigital forms. It exhibits a high capacitance of up to 68.3 F cm −3 and a superior cycling stability with 98% capacitance retention after 25 000 cycles. Most importantly, the SSA technique enables the CmSC as the building block to realize arbitrary, programmable, and multi‐dimensional integration for adaptable and complicated power systems. By design on mortise and tenon joint connection, autologous integrated 3D interdigital CmSCs are fabricated in a self‐holding‐on manner, which thus dramatically reduces the whole device volume to achieve the high‐performance capacitive behavior. Consequently, the SSA technique offers a universal and versatile approach for large‐scale on‐demand integration of mSCs as flexible and transformable power sources. Abstract : A versatile self‐shrinkage assembly strategy is developed to directly construct a compact microsized supercapacitor (CmSC) from hydrogels of reduced graphene oxide. A single CmSC features a low volume of only 0.0023 cm 3 but an unprecedented capacitance. The CmSCs can be shaped into various geometries and work effectively as building blocks for programmable integration toward mSC systems.